Khách
Khách

Hãy nhập câu hỏi của bạn vào đây

3 giờ trước (10:37)

x = \(\dfrac{2}{-5}\) = - \(\dfrac{2}{5}\) = \(\dfrac{-14}{35}\)  > \(\dfrac{-15}{35}\) = - \(\dfrac{3}{7}\)

x > y 

4 giờ trước (9:31)

`27^5:x=9`

`(3^3)^5:x=3^2`

`3^{15}:x=3^2`

`x=3^{15}:3^2`

`x=3^{15-2}`

`x=3^13`

16 giờ trước (20:44)

Theo mình đoán thì chắc ý bạn là 

\(\dfrac{x+5}{2005}+\dfrac{x+6}{2004}+\dfrac{x+7}{2003}=-3\)

\(\Leftrightarrow\left(\dfrac{x+5}{2005}+1\right)+\left(\dfrac{x+6}{2004}+1\right)+\left(\dfrac{x+7}{2003}+1\right)=0\)

\(\Leftrightarrow\dfrac{x+2010}{2005}+\dfrac{x+2010}{2004}+\dfrac{x+2010}{2003}=0\)

\(\Leftrightarrow\left(x+2010\right)\left(\dfrac{1}{2005}+\dfrac{1}{2004}+\dfrac{1}{2003}\right)=0\)

\(\Leftrightarrow x=-2010\) hay \(\dfrac{1}{2005}+\dfrac{1}{2004}+\dfrac{1}{2003}=0\left(vôlí\right)\)

Vậy \(x=-2010\)

17 giờ trước (20:24)

\(\dfrac{1}{5}\) . 2x + \(\dfrac{1}{3}\) . 2x + 1 = \(\dfrac{1}{5}\) . 27 + \(\dfrac{1}{3}\).28

2x.( \(\dfrac{1}{5}\) + \(\dfrac{2}{3}\)) = 27.(\(\dfrac{1}{5}\) +\(\dfrac{2}{3}\))

2x = 27

x = 7